Estetisasi Jilbab Syar’i Jama’ah Salafi: Studi Kasus di Pondok Pesantren Imam Muslim Kota Kediri - Mahanani, Prima Ayu Rizqi; Abdullah, Irwan; Noviani, Ratna (JSW (Jurnal Sosiologi Walisongo), 2019)
Industry of fashion that get into the life of Salafi members makes shar'i hijab become aesthetics. Approximately 30% of Salafi women in Imam Muslim Islamic Boarding School Kediri have worn hijab shar?i as their preference. This article describes the aesthetic practices of shar?i hijab and the factors behind it. This study applies a qualitative approach using a case study as a research method in which it observes the social reality of shar?i hijab aesthetic practices among Salafi women at Imam Muslim Islamic Boarding School. The research analyzes the case and situation that occurred and also attempts to understand the informants? point of view. Through literature studies, participatory observation, and in-depth interviews, the study found that the informants have been wearing two different shar?i hijab; dark colors and bright colors. The informants also combine their "gamis" in terms of its pattern consisting of ornaments and accents in different colors. The informants also prefer to wear a unique and funny, in order to make them look flexible, younger and up to date.